Vertical Distribution of Ozone and Nitrogenous Pollutants in an Air Quality Class I Area, the San Gorgonio Wilderness, Southern California - Alonso, Rocio (ScientificWorldJournal, 2002)
Information about spatial and temporal distribution of air pollutants is essential for better understanding of environmental stresses affecting forests and estimation of potential risks associated with air pollutants. Ozone and nitrogenous air pollutants were monitored along an elevation gradient in the Class I San Gorgonio Wilderness area (San Bernardino Mountains, California, U.S.) during the summer of 2000 (mid-June to mid-October). Passive samplers were exposed for 2-week periods at six sampling sites located at 300 m intervals ranging from 1200 to 2700 m elevation. Elevated concentrations of ozone were found in this area with summer 24-h hourly means ranging from 53 to 59 ppb. The highest ozone concentrations were detected in the period July 25 to August 8, reaching values of 64 to 72 ppb expressed as 2-week mean. Passive-sampler ozone data did not show a clear relationship with elevation, although during the periods with higher ozone levels, ozone concentrations were higher at those sites below 2000 m than at sites located above that elevation. All nitrogenous pollutants studied showed a consistent decrease of concentrations with elevation. Nitrogen dioxide (NO(2)) levels were low, decreasing with increasing elevation from 6.4 to 1.5 ppb summer means. Nitric oxide (NO) concentrations were around 1 to 2 ppb, which is within the range of the detection levels of the devices used. Nitric acid (HNO(3)) vapor concentrations were lower at higher elevations (summer means 1.9 to 2.5 μg m) than at lower elevations (summer means 4.3 to 5.1 μg m). Summer concentrations of ammonia (NH(3)) were slightly higher than nitric acid ranging from 6 μg m at the lowest site to 2.5 μg m registered at the highest elevation. Since complex interactions between ozone and nitrogenous air pollutants have already been described for forests, simultaneous information about the distribution of these pollutants is needed. This is particularly important in mountain terrain where no reliable models of air pollutant distribution exist.